PELATIHAN LONCAT TEGAK TANPA AWALAN LEBIH MENINGKATKAN DAYA LEDAK OTOT TUNGKAI DARIPADA PELATIHAN LOMPAT BERGANTIAN - Joppi Huwae; Ketut Tirtayasa; Oktovianus Fufu; N. Adiputra; Bagus Komang Satriyasa; Susy Purnawati (Program Studi Magister Fisiologi Keolahragaan, Fakultas Kedokteran, Universitas Udayana, 2017)
Background: Explosive power is the ability of a person to overcome the resistance with a high-speed contraction. This capability is necessary not only in the physical activities of sport but also in situations of physical activity events. Objective: To achieve the necessary exercise continuous and systematic training jump and jump straight without leading alternately (Plyometrik). Exercise jump and jump in essence aims to spur and stimulate repulsion leg so strong that generate maximum explosive power. This study was to compare the exercise group jump upright without proclitic and alternately jump to the explosive power of leg muscle. Method: The study was a randomized experiment design with pretest- posttest control group design of student PJKR PGRI University-Kupang, with a sample of 28 people, divided into two groups and each group totaled 14 people. Group-1 given vertical jump training without the first and second group of jump training alternating with 3 sets of 5 reps done during 8 weeks with a frequency of exercise three times per week.Muscle explosive power measurement with high stepping unprefixed. Measurements were performed before and after treatment. The results of the research in using the Shapiro-Wilk normality test and homogeneity test with Leven's Test. Result: Paired t-test to determine the differences mean an increase in leg muscle explosive power in group 1 jump straight with no proclitic (LTTA) with a mean pre-training = 41.4 ± 1.0 cm, and the mean after training = 64.1 ± 2.7 cm the difference = 22.7 cm and the percentage increase = 54.8% (p <0.05). Whereas in the group 2 alternately jump (LB) with a mean pre-training = 41.4 ± 0.80 cm, and mean after training = 49.8 ± 1.7 with difference = 8.4 cm and the percentage increase of 20.28% = (p<0.05). Effects comparison results Improve Limb Muscle Burst in the t-independent test between groups before and after training at the limit of significance ? = 0.05. The mean increase explosive power leg muscle before training with a value of p> 0.05, which means that the initial condition is the same training and after the training has a value of p <0.05. It can be concluded that the two groups together to give the effect of increased leg muscle explosive power with increased high-stepping (p <0.05). Conclusion: But the increase in group 1 vertical jump training without the proclitic (LTTA) better than in group 2 jump alternately by a margin percentage is greater then the increase of leg muscle explosive power is greater. Suggestion: Suggested that sports that require explosive power leg muscle in order to use the vertical jump training without the proclitic.